Interpretation of effect estimates in competing risks survival models: A simulated analysis of organ-specific progression-free survival in a randomised phase III cancer trial - Virdee, P; Dutton, P; Love, S; Wasan, H; Sharma, R; Moschandreas, J (2016)
A presentation encouraging the reporting of all competing risk estimated hazard ratios to provide a more complete picture of the treatment effect on patients